Comparison of the two most commonly used gold-standard velocity monitoring devices (GymAware and T-Force) to assess lifting velocity during the free-weight barbell back squat exercise - Janicijevic, D.; García-Ramos, A.; Lamas-Cepero, J. L.; Garcia-Pinillos, F.; Marcos-Blanco, A.; Rojas, F. J.; Weakley, J.; Perez-Castilla, A. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2023)
This study aimed to compare the reliability and agreement of mean velocity (MV) and maximal velocity (Vmax) between the two velocity monitoring devices (GymAware vs T-Force) most commonly used in the scientific literature. Twenty resistance-trained males completed two testing sessions. The free-weight barbell back squat one-repetition maximum (1RM) was determined in the first session (125.0 ± 24.2 kg; mean ± standard deviation). The second session consisted of two blocks of 16 repetitions (six repetitions at 45% 1RM and 65% 1RM, and four repetitions at 85% 1RM). Half of the repetitions were performed with the GymAware on the left side of the barbell and the other half of the repetitions were performed on the right side of the barbell (opposite placement for the T-Force). MV and Vmax were recorded simultaneously with the GymAware and T-Force. The overall reliability, which was calculated pooling together the data of three loads, did not differ between the T-Force (coefficient of variation (CV) = 5.28 ± 1.79%) and GymAware (CV = 5.79 ± 2.26%) (CVratio = 1.10), but the reliability was higher for Vmax (CV = 5.08 ± 1.79%) compared to MV (CV = 5.98 ± 2.73%) (CVratio = 1.18). MV was significantly higher for the T-Force (p < 0.001, ? = 4.42%), but no significant differences were detected between the devices for Vmax (p = 0.455, ? = 0.22%). These results support the use of both the GymAware and T-Force as gold-standards in studies designed to validate other velocity monitoring devices. However, systematic bias, albeit rather constant, exists for the magnitude of MV between the two devices.